Analisa Studi Kelayakan Penambahan Mesin Vessels Dengan Metode NPV Di PT XYZ Karawang - Bima Setyo; Syifa Pramudita (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
PT XYZ Karawang is required to increase its production capacity by adding vessel machines to meet this (demand), and as one of PT XYZ Karawang's strategies to develop its business. The addition of this production machine is planned in order to reduce potential losses such as maintenance costs and prevent production delays that have been set. The purpose of this research is to ascertain whether an investment plan to be implemented is economically viable or not. This data collection was taken from secondary and primary data at PT. XYZ Karawang. Results NPV analysis results and data processing value of the old machine NPV 80,798.1 > new machine NPV 10,977.32. The results of PP analysis and processing of data on the value of the old PP machine required 3.9 years < new machine PP the value of the new machine. The results of the PI analysis and data processing of the value of the old machine PP 26.9 > the PI of the new machine 7.32. So the suggestion from the conclusion above is that the investment decision to add fixed assets (new machine vessels) is feasible to carry out to increase surfactant production capacity whose sales value continues to increase from year to year.